REFLEXIVE APPROACH-BASED DEVELOPMENT OF SPIRITUAL CONSCIOUSNESS (International journal of artificial intelligence, 2026)
This article examines the theoretical and practical significance of developing spiritual consciousness through a reflexive approach within modern educational and social contexts. In the era of globalization, digital transformation, and rapid sociocultural change, the formation of spiritual consciousness has become one of the central priorities of educational philosophy and human development. The reflexive approach allows individuals to critically evaluate their values, beliefs, behaviors, and moral responsibilities through self-awareness and introspection. The study explores the role of reflective thinking in shaping ethical responsibility, personal identity, cultural understanding, and social harmony. Furthermore, the article analyzes how reflexive mechanisms contribute to the formation of moral maturity, independent thinking, emotional intelligence, and intercultural competence among students and young people. The research highlights the pedagogical potential of reflexive learning strategies in strengthening spiritual values and humanistic worldviews. The article also discusses the influence of reflective dialogue, self-analysis, critical consciousness, and value-oriented education in the development of spiritually mature individuals capable of responding to contemporary global challenges.